(untitled) (Semiárida, 2020)
Voluntary intake (OMI) and digestibility (OMD) of organic matter were estimated on a deferred pasture of Panicum coloratum L., using grazing rams, by two different methods. Four treatments, corresponding to tour forage allowances (in g. DM. Kg-1 ot liveweight.day-1) were established: T1: 15; T2: 30; T3: 45; T4: 60. Six Pampinta rams by treatment grazed during 22 days, being the last 6 days the measurement period The first method estimated OMI as the difference between initial and final biomass (OMldir), and digestibility (OMDdir) from OMldir, and fecal organic matter production (F). The second method of estimation used Iignin as internal marker. The organic matter digestibility (OMO was estimated through the concentrations of Iignin in diet and faeces, and the voluntary intake (OMILDA), from (OMDLDA) and F. No differences (p>0.05) between treatments could be detected in any of the measured variables. The OMI, as estimated through both methods, were highly correlated (r = 0.97; p<0.01). II seems Iikely that Iignin ls a suitable internal marker in Panicum coloratum L. Both, digestibility and voluntary in lake of grazing animals can be estimated through this technique, with good precision.